Factor influence customer usage of mobile banking services provided by Bank Islam Malaysia Berhad: a case study in Selangor / Mohamad Arief Salsabiluddin Ranili - Ranili, Mohamad Arief Salsabiluddin (Faculty of Business Management, 2017)
This study is to determine the factors that affect the acceptance of the use of mobile banking provided by Bank Islam Malaysia Berhad. These factors are divided into two groups according to their impact, the first represents the factors that drives the customers to use mobile banking services, they are assurance, ease of use communication, speed of transaction and pursuance. The second are factors that prevent the use of mobile banking services; it imcludes personal desires, knowledge, habit, resistance to innovations and experience. There are 100 questionnaires prepared and will be distributed to the targeted respondents in the Selangor area. SPSS software will be used to generate the data to get the result.